1986
DOI: 10.1148/radiology.160.3.3526400
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease: sonographic appearance of the spleen.

Abstract: Ultrasonographic (US) examinations of the upper abdomen were performed in 80 patients with Gaucher disease. Of the 49 patients that had not undergone splenectomy, 47 had splenic enlargement. Sixteen patients had multiple lesions in the spleen. Most patients had discrete hypoechoic lesions that corresponded pathologically to focal homogeneous clusters of Gaucher cells. Several patients had similar lesions that were hyperechoic and were composed of Gaucher cells and fibrosis or infarction. A few patients had a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…The radiographic manifestations of type 1 Gaucher disease are well known [8,[16][17][18][19]. Data presented here reveal a similar distribution of abnormalities in patients with type 3 b Gaucher disease.…”
Section: Discussionsupporting
confidence: 72%
“…The radiographic manifestations of type 1 Gaucher disease are well known [8,[16][17][18][19]. Data presented here reveal a similar distribution of abnormalities in patients with type 3 b Gaucher disease.…”
Section: Discussionsupporting
confidence: 72%
“…There were no changes in the numbers of lesions or their characteristics during the evaluation period in patients receiving enzyme treatment. The low percentage of splenic lesions noted contrasts with the finding of splenic lesions in 16 adult patients with Gaucher disease in a cohort of 49 patients (32.7 %) evaluated by sonography [7]. In these adults all lesions were multiple, with the majority being hypoechoic.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it has been extrapolated that splenic lesions, although apparently uncorrelated with the severity of other disease parameters or genotype, may be part of the natural history of the disease in some patients and is correlated with degree of organomegaly or age [8]. On the other hand, no sonographic abnormalities were found in the livers of the 80 adult patients in that series [7], which is dissimilar to our current pediatric cohort and to the finding of 6 % hepatic lesions among 218 consecutive patients, adults, and children from our clinic [8].…”
Section: Discussionmentioning
confidence: 92%
“…The underlying cause of thrombocytopenia related to spleen size is unclear from this study, but may not necessarily involve only increased platelet destruction in the spleen. Other contributory factors may include a pooling effect where the enlarged spleen acts as a reservoir to take platelets out of the general circulation (Aster, 1966); and/or prolonged delay before the initiation of therapy leading to irreversible spleen changes, such as fibrosis (Lee, 1982;Hill et al, 1986;Iwanami et al, 1992) or changes in vascularization, which could prevent the therapeutic enzyme from reaching Gaucher cells (Pastores et al, 2004;Stein et al, 2010;Mistry et al, 2007;de Fost et al, 2008). A study has shown that focal lesions in the spleen are associated with suboptimal splenic and platelet responses to imiglucerase therapy (Stein et al, 2010).…”
Section: Figmentioning
confidence: 99%